Effect of Adding Moringa Leaf Flour on the Sensory Acceptance of Moringa Biscuits - Meliana, Anita; Junaidi, Junaidi (Jurusan Gizi, Poltekkes Kemenkes Aceh, 2025)
The Recovery Food Supplement (PMT) program is a government initiative aimed at improving the nutritional status of toddlers by providing food supplements in addition to their daily intake, particularly for undernourished children. One form of PMT is the toddler biscuit, formulated to contain a minimum of 160 kcal, 3.2–4.8 g of protein, and 4–7.2 g of fat per 40 g serving. According to technical guidelines, PMT targets children aged 6–59 months who are categorized as underweight (weight-for-height < –2 SD) and is administered for 90 days. To determine the effect of adding Moringa leaf flour on the acceptability of Moringa-based biscuit snacks. This study employed a non-factorial Completely Randomized Design (CRD) with three treatments: Y1 (40 g cornstarch + 10 g Moringa leaf flour), Y2 (40 g cornstarch + 15 g Moringa leaf flour), and Y3 (40 g cornstarch + 25 g Moringa leaf flour). Organoleptic tests assessed color, taste, aroma, and texture parameters. Data were analyzed using ANOVA. ANOVA results showed no significant effect on color (p = 0.216), aroma (p = 0.753), or texture (p = 0.877). However, a significant difference was found in the taste parameter (p = 0.034), indicating that the addition of Moringa leaf flour influenced the flavor of the biscuits. The addition of Moringa leaf flour significantly affected the taste of Moringa biscuit snacks but had no significant effect on color, aroma, or texture. Future research should consider using a standardized baking temperature across all treatments and explore higher concentrations of Moringa leaf flour to enhance the nutritional content of the product.